Total Rewards: Addressing the Challenges of Today’s Workplace - Binghay, Virgel C. (Philippine Journal of Labor and Industrial Relations, 2021)
In light of developments in today’s global market, the competition to attract, engage and retain talent has become even stiffer for companies. Generational shifts in the workplace have also changed employer-employee dynamics, from a paternalistic relationship to one wherein employees seek growth and development for their careers. Total rewards can be a crucial strategy in this highly volatile market. It goes beyond mere compensation and extrinsic remuneration and considers the overall employee experience in the workplace. It is a business strategy that focuses on getting and keeping the best people in the team by providing a holistic rewards model which encompasses compensation, benefits, work-life balance, performance and recognition, and development opportunities. In the end, it drives to the heart of human resource management by taking care of people so that they in turn will take care of the business.